Efeito da calagem na dispersão de argila em um latossolo vermelho-escuro - Jucksch, Ivo; Marciano da Costa, Liovando; Moura Filho, Waldemar; Ribeiro, Antônio Carlos; Soprano, Eliséo (Revista Ceres, 2025)
The aim of this study was to evaluate clay dispersion by lime. Several rates and sources of liming materials were tested in Dark Red Latosol with high aluminium saturation. The mixtures used were the following: calcium carbonate plus magnesium carbenate, calcium sulfate plus magnesium carbonate, and calcium chloride plus magnesium chioride. The calcium to magnesium ratio was 4:1 for all treatments used in this study. The soil and liming materials were placed in contact for nine months. The samples were subsequently stirred with water and left to rest for 24 hours so that the clay dispersion might be measured. The clay remained dispersed after this period of time in the case of the carbonate compounds applied to the soil samples. 1t was concluded that dispersion of soil with high aluminium saturation brings on physical soil modifications in the layer under the Ap horizon.